2021
DOI: 10.3389/fonc.2021.754221
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine CXCL7 Is Related to Angiogenesis and Associated With Poor Prognosis in Colorectal Cancer Patients

Abstract: ObjectiveThe present study was designed to investigate the role of the chemokine CXCL7 in angiogenesis and explore its prognostic value in colorectal cancer (CRC).MethodsA total of 160 CRC patients who had undergone surgery were included in this study, and staged according to the guidelines of the AJCC, 7th Edition. Expression of CXCL7 and VEGF was detected by immunohistochemical (IHC) staining and divided into high and low expression subgroups. The correlation between CXCL7 and VEGF expression was evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 60 publications
5
24
0
Order By: Relevance
“…1A, B vs. 1C, D). As this result was similar to that of our previous study (20), a score of 3.5 was regarded as the cut-off value for CXCL7 expression on the basis of the ROC curve. The protein level of LDH-A was also increased in cancer cells compared with normal tissue cells (56.96%, 90/158 vs. 18.99%, 30/158; P < 0.001; Fig.…”
Section: Elevated Expression Of Cxcl7 and Ldh-a In Crc Tissuessupporting
confidence: 74%
See 1 more Smart Citation
“…1A, B vs. 1C, D). As this result was similar to that of our previous study (20), a score of 3.5 was regarded as the cut-off value for CXCL7 expression on the basis of the ROC curve. The protein level of LDH-A was also increased in cancer cells compared with normal tissue cells (56.96%, 90/158 vs. 18.99%, 30/158; P < 0.001; Fig.…”
Section: Elevated Expression Of Cxcl7 and Ldh-a In Crc Tissuessupporting
confidence: 74%
“…Recurrence and metastasis are the most important causes of cancer-related deaths. Numerous oncogenes, tumor suppressor genes, cytokines, and chemokines have been shown to have important roles in the processes of recurrence and metastasis (8, 13,20,23). Previous studies have proved that glycolysis plays critical parts in tumor progression, especially in recurrence and metastasis (37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…In CRC, high expression of CXCL7 is closely associated with tumor vascular production. Previous studies have shown that CXCL7 is positively correlated with VEGF and that the coexpression of CXCL7 and VEGF is a risk factor for a poor prognosis in CRC patients ( Li et al, 2021 ).…”
Section: The Biological Characteristics Of Cxcl7mentioning
confidence: 99%
“…There is growing evidence indicating that CXCL7 is expressed by a variety of tumors, including renal cell carcinoma, breast cancer, and colorectal cancer, and that its aberrant expression can serve as a valid marker for multiple systemic malignancies, thus helping clinicians in early identification of malignancies and monitoring of treatment efficacy ( Wang et al, 2013 ; Dufies et al, 2017 ; Li et al, 2021 ). By binding to CXCR1 and CXCR2, CXCL7 can affect tumor proliferation, invasion, migration, and tumor angiogenesis in an autocrine and paracrine manner through multiple signaling pathways ( Wang et al, 2013 ; Mollica Poeta et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relation between loss of Mothers Against Decapentaplegic Homolog 4 (SMAD4) in human colorectal cancer cells and tumor-infiltrating immune cells and its chemokines and receptors. and some chemokine receptors are also associated with angiogenesis (49)(50)(51)(52)(53). For instance, CCR6 is found significantly overexpressed in CRC tissues and facilitates tumor angiogenesis via the AKT/NF-kB/VEGF pathway (54).…”
Section: Endothelial Cellsmentioning
confidence: 99%